2007
DOI: 10.1016/j.jinsphys.2007.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Induction of actin gene expression in the mosquito midgut by blood ingestion correlates with striking changes of cell shape

Abstract: Ingestion of a blood meal by the female mosquito Anopheles gambiae (L., Diptera: Culicidae), results in a dramatic distention of the midgut epithelium. Here we report that these events correlate with a transient increase of actin mRNA and protein abundance. The newly synthesized actin may provide a pool of actin protein needed to remodel epithelial cell cytoarchitecture. We also document changes in midgut epithelial cell morphology. Upon blood ingestion, the columnar cells flatten accompanied by the loss of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…These results suggest that the effects of P. berghei killing are independent of the host blood meal, and more likely caused by the distention of the mosquito midgut following feeding. Ingestion of a blood- or protein-meal results in dramatic changes to midgut epithelium cell morphology, causing a flattening of the columnar cells, the loss of microvilli, and substantial degradation of the basal lamina (Dong et al, 2017; Sodja et al, 2007). This agrees with our CHP assays demonstrating the presence of degraded collagen shortly after taking a blood- or protein-meal, suggesting that the integrity of the basal lamina is compromised during distention, enabling the exposure of developing oocysts to components of the mosquito hemolymph.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the effects of P. berghei killing are independent of the host blood meal, and more likely caused by the distention of the mosquito midgut following feeding. Ingestion of a blood- or protein-meal results in dramatic changes to midgut epithelium cell morphology, causing a flattening of the columnar cells, the loss of microvilli, and substantial degradation of the basal lamina (Dong et al, 2017; Sodja et al, 2007). This agrees with our CHP assays demonstrating the presence of degraded collagen shortly after taking a blood- or protein-meal, suggesting that the integrity of the basal lamina is compromised during distention, enabling the exposure of developing oocysts to components of the mosquito hemolymph.…”
Section: Discussionmentioning
confidence: 99%
“…Adults were collected 3 days after emerging from pupae. The adults fed with a blood meal were collected three hours later so that the genes responding to blood ingestion were sufficiently expressed [149]. Samples were homogenized with a dounce homogenizer and RNA was isolated from tissue homogenate with an RNeasy Midi kit (Qiagen).…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, upregulation of an actin-like gene was detected at 6h PBM. It was previously reported that increased levels of actin mRNA at 3-4h PBM correlates with epithelial remodeling to accommodate distention of the midgut upon blood ingestion [20]. As SCD1 KD causes rigidity of the epithelial cell membranes, this is suggestive of a stress response to overcome the mechanical pressure caused by the rigid cell membranes.…”
Section: Cytoskeleton Cell Adhesion and Structural Componentsmentioning
confidence: 85%
“…Noteworthily, cell membrane thickness in SCD1 KD midguts was only marginally reduced after bloodmeal (60 nm compared to 55 nm respectively). Reduction of cell membrane thickness is a known adjustment to the expansion of the epithelial cell surface in order to provide structural support to the engorged midgut epithelium [20]. We conclude that SCD1 loss-of-function alters the ability of midgut epithelial cells to undergo adjustments needed to offset the increased pressure within the lumen, causing rapturing of the epithelial cell layer upon blood feeding and blood perfusion of the thoracic cavity.…”
Section: Scd1 Silencing Affects Midgut Epithelial Integrity and Egg Dmentioning
confidence: 90%